Comparing the effects of agricultural intensification on CO2 emissions and energy consumption in developing and developed countries - Khan, Rabnawaz; Alabsi, Akram Ahmed Noman; Muda, Iskandar (Frontiers in Environmental Science, 2023)
Energy consumption has become a requirement in the modern world, and without it, the economies of developing nations cannot prosper. Consistent economic growth is a challenge for countries of all economic levels, not just the less developed ones. We test the EKC hypothesis by analyzing the relationships between GDP growth, energy consumption, agricultural output, and the consequences of carbon dioxide (CO2) emissions. From 1991 to 2016, we used panel and quantile regression analysis to compare emissions in 9 developing countries with those in 13 developed countries. There is the beginning of a reverse U-shaped relationship between agricultural energy use and greenhouse gas emissions. As a result, the verified EKC hypothesis paves the way for a watershed moment in the progress of industrialized nations' economies. As an added bonus, agricultural results have a positive impact on CO2 emissions from using liquid fuels. It has a negative impact on CO2 emissions by 19.12% and causes a 4.802 percent increase in environmental degradation. Feed cropping, deforestation, biomass burning, and deep soil and cropping also have negative effects on the environment, especially in developing countries. There is a negative correlation between CO2 emissions and economic growth in developing countries and their energy consumption. Although the EKC hypothesis for CO2 emissions was rejected at lower quantiles, it was validated for Qatar, Canada, China, and other high-emitting economies according to the empirical estimation of quantile regression. The findings of this study have important policy implications for reducing carbon dioxide emissions, suggesting that policymakers account for the stage of economic growth currently being experienced when formulating measures to cut energy use and protect the environment. In particular, policies aimed at reducing energy consumption could.